A key management scheme realising location privacy protection for heterogeneous wireless sensor networks. (12th January 2020) - Yuan, Erdong; Wang, Liejun
Key management is the core of wireless sensor network (WSN) security management technology. At present, the protection of the source location information of nodes has also received great attention. In this paper, we combine identity-based encryption (IBE) algorithm with elliptic curve cryptography (ECC) based digital signature authentication to achieve more secure authentication. Then we use the double encryption method to realise the location privacy protection. Finally, we adopt a new routing update scheme to prevent attackers from initiating sinkhole attacks. In addition, we add timestamps to messages transmitted between nodes to defend against resend attacks. The scheme we proposed occupies a small amount of key storage space, consumes relatively more energy to protect the location information of nodes in the heterogeneous sensor network (HSN), and prevents attackers from initiating sinkhole attacks and resend attacks, thereby enhancing network security.